Catalyzing Private Sector Investment in Climate Smart Cities - World Bank; United Nations Development Programme; Global Infrastructure Facility (World Bank and United Nations Development Programme, 2021)
The objective of this report is to explore innovative financing instruments and approaches for catalyzing private sector financing to fill the climate-smart investment gap in cities. The report reviews the existing literature, highlights key barriers in scaling-up private investment in climate-smart urban infrastructure, and showcases innovative financial de-risking instruments and other financial instruments for private sector financing for low carbon, resilient urban investments. The first chapter of the report introduces the topic and the second presents the challenges and the opportunities of urban climate investments. The third chapter discusses climate-smart cities and types of urban mitigation and resilience investments. The fourth chapter reviews and provides a framework to examine the interconnected layers of investment barriers specific to private investment, city financing, and climate-smart projects. Considering these risks allows investors and other stakeholders to better understand the complex web of challenges to expanding investment in urban climate projects and how they build on one another. Chapter five presents 10 case studies of innovative financing approaches to address some of these barriers and mobilize private sector finance for low carbon, resilient urban development. Finally, the conclusion in chapter six offers some key findings and considerations for the wider community of practice.